PHARMACOTHERAPY OF OVERACTIVE BLADDER: A 10 YEARS SYSTEMATIC REVIEW - Ramadhani, Rizkia Amal; Fithri Rofifa, Amira (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: OAB is a stigmatized condition that significantly affects quality of life. The current first-line pharmacological approach to treating OAB involves various medications, primarily antimuscarinic agents and adrenoceptor agonist. This study aims to provide a 10 year systematic review of pharmacological approach in OAB treatment. Methods: This systematic review adhered to the PRISMA 2020 standards and included full-text English literature published between 2014 and 2024. Exclusion criteria involved editorials, review articles from the same journal, and submissions lacking a DOI. Literature was gathered from online sources such as PubMed and SagePub. Result: Our search in PubMed yielded 997 articles, while SagePub produced 357 articles. Focusing on the last 10 years (2014-2024), PubMed had 667 articles and SagePub had 160 articles. Ultimately we selected 5 papers that met our criteria, 3 from PubMed and 2 from SagePub. Conclusion: Due to the the improvements in urgency, frequency, and incontinence as well as fewer treatment-related adverse events, adrenoceptor agonist mirabegron is recommended as the first-line treatment for OAB.